TAX AVIODANCE DAN FAKTOR DETERMINAN PADA PERUSAHAAN PERTAMBANGAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BEI - Rina Tjandrakirana; Ermadiani Ermadiani; Anton Indra Budiman (AKUNTABILITAS, 2022)
This study aims to determine and test the factors that influence tax avoidance in the coal mining subsector. In this study, tax avoidance is measured using the Effective Tax Rate (ETR) as the dependent variable. This study uses a sample in the form of financial reports from coal mining companies listed on the Indonesian stock exchange for the period 2014-2019. The research sample was determined by purposive sampling technique, in order to obtain 9 companies that met the requirements as samples. Data analysis was carried out by classical assumption test and hypothesis testing using multiple linear regression method. The results of this study indicate that the factors that influence tax avoidance in coal mining companies, namely company size, independent commissioners, and audit quality have an effect on tax avoidance. Meanwhile, Leverage has no effect on tax avoidance.